Comparative Study of Modification of Woods by Chemicals Against a White Rotter Tramates versicolor - Mohanty, Manoranjan; Sharma, Ashwini Kumar; Sharma, Ramesh Chand (Indian Forester, 2001)
Durable primary timber species and heartwoods are becoming scarce, hence secondary timber species and sap woods are of next choice. As biodegradation is chemical in nature, only chemical modification of wood that primarily changes the site of action for the fungal enzyme for which the organism can not recognise it, can protect the wood against the degradation. Chromic acid treatment was superficial one whereas sodium periodate penetrated into the wood matrix. Decay loss due to fungus (Tramates versicolor, white-rotter) decreased with increase in NaIO4 concentration in all the three wood species. At 1.0% NaIO4for 20h dip, no decay loss was observed in any wood. Chromic acid application (5.0% for 5 min) also showed reduced fungal decay. But 0.5% of NaIO4 for 20 h dip was more effective than the chromic acid treatment. Combined treatment (NaIO4 followed by CrO3 application) was superior to all other treatments as no decay loss was for 1.0% concentration of NaIO4 for 20 h dip in B. ceiba and C. australis and 0.5% concentration of NalO4 for 20 h dip in P. deltoides.